2011
DOI: 10.1007/s00417-011-1869-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal drugs prevent posterior capsular opacification in human lens capsule in vitro

Abstract: Background To determine whether the cytoskeletal drugs H-7 and Latrunculin B (LAT-B) inhibit posterior capsular opacification (PCO) in the cultured human lens capsular bag. Methods Following extracapsular cataract (lens) extraction in human donor eyes, the capsular bag was prepared and cultured by standard techniques. Forty-eight capsular bags were studied, in which 13 were treated with H-7 (50, 100 or 300μM), 12 with 1% BSS (vehicle of H-7), 11 with LAT-B (2, 5 or 10μM), and 12 with 0.25% DMSO (vehicle of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…49 As expected capsular wrinkling can be inhibited by treatment with the actin depolymerizing agent, latrunculin B. 50 Although latrunculin B can inhibit capsular wrinkling, it is a potent G-actin sequestering agent, and nondiscriminately disassembles dynamic F-actin networks. By targeting Tpm3.1, the F-actin stress fibers at the basal regions of epithelial cells adjacent to the lens capsule can be selectively targeted, possibly leading to reduced capsular wrinkling.…”
Section: Discussionmentioning
confidence: 79%
“…49 As expected capsular wrinkling can be inhibited by treatment with the actin depolymerizing agent, latrunculin B. 50 Although latrunculin B can inhibit capsular wrinkling, it is a potent G-actin sequestering agent, and nondiscriminately disassembles dynamic F-actin networks. By targeting Tpm3.1, the F-actin stress fibers at the basal regions of epithelial cells adjacent to the lens capsule can be selectively targeted, possibly leading to reduced capsular wrinkling.…”
Section: Discussionmentioning
confidence: 79%
“…include 5-fluorouracil, methotrexate, colchicine, mitomycin, 31,44 protease inhibitors, 13,27,45 cytoskeletal drugs, 46 aldose reductase inhibitors, 43 chelators, 47 small interfering RNAs, 48 and signal transduction inhibitors. 49 Gene transfer techniques also have been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…128 It has also been observed that PCO can be inhibited in vitro by using pharmaceutical agents targeting the cytoskeleton. 129 The cytoskeleton is typically involved in transducing external mechanical cues. Thus, inhibiting this mechanosensation in LECs may disrupt cytoskeleton-based signalling activity and potentially decouple the cellular response from mechanotransductive signals.…”
Section: Lec Mediated Lens Regenerationmentioning
confidence: 99%